The Agrarian Question and the Neoliberal Rural Transformation in Latin America. - Kay, Cristóbal (European Review of Latin American & Caribbean Studies, 2015)
Since the neoliberal turn in Latin America the rural economy and society has experienced a great transformation. Corporate capital and transnational agro-industries have taken hold of agriculture radically transforming the economic and social relations of production leading to the precarization and feminisation of rural labour as well as the intensification of work. Peasant farmers were further squeezed having to increasingly find off-farm incomes, largely through precarious wage labour activities, so as to make a living thereby furthering the process of proletarianization. The 'new rurality' and 'territorial' approaches tried to take account of these transformations but they are found wanting. Instead, a political economy view to the agrarian question is found more promising. A counter-movement to neoliberalism has emerged spearheaded by indigenous peoples and the rural poor, sometimes linked to the transnational peasant movement 'Via Campesina'. Their main aim is to construct an alternative agrarian system based on 'food sovereignty' which is promising but also controversial.